The Thyristor Electronic Transformer: a Power Converter Using a High-Frequency Link - McMurray, William (IEEE transactions on industry and general applications, 1971)
The electronic transformer is a device which behaves in the same manner as a conventional power transformer in that it steps voltage levels up or down while providing isolation and can accommodate load current of any power factor. It contains thyristor power switches which convert the low-frequency (dc to 400-Hz) voltage wave to a high-frequency (in the order of 10 000 Hz) wave. A comparatively small magnetic transformer then provides the voltage level transformation and isolation functions. Similar thyristor power switches then reconstruct the original low-frequency wave at the desired output voltage level. This device can incorporate additional features not found in a conventional transformer, such as current limiting and current interruption. The theory of operation is presented and confirmed by experimental data.